Maternal mortality cases due to COVID-19 pandemic in a tertiary referral hospital - Şeyhmus Tunç; Süleyman Cemil Oğlak; Mehmet Rıfat Göklü; Zeynep Gedik Özköse (Perinatal Medicine Foundation, 2022)
Objective: This study aimed to report the clinical prognoses, laboratory findings, treatment procedures, and neonatal outcomes, from hospitalization to death, of Coronavirus Disease 2019 (COVID-19)-related cases of maternal mortality at our clinic. Methods: Fifteen cases of COVID-19-related maternal mortality, between April 2020 and October 2021, in the Department of Obstetrics & Gynecology of a Training and Research Hospital were retrospectively analyzed for the purpose of the study. Results: During the study period, a total of 501 symptomatic pregnant women received inpatient treatment for COVID-19. In our case group, 93.3% of maternal deaths due to COVID-19 occurred as a result of the worsening of the clinical condition of third-trimester pregnant women. In these patients whose clinical condition deteriorated, delivery was performed after the decision to give birth, and 86.6% of mortalities occurred in the postpartum period and 13.4% before delivery. There was at least one risk factor in 60% of the cases, with obesity being the most prevalent. In all mortality cases, there were pulmonary complaints (shortness of breath and cough) at admission, and bilateral lung involvement was observed during lung imaging; furthermore, there was a corresponding increase in the mean leukocytosis, AST, ALT, LDH, D-dimer, ferritin, procalcitonin, IL-6, and pro-BNP levels with the worsening of the clinical prognosis. The duration of hospitalization and intensive care unit stays were 6.87±3.18 and 5.33±3.27 days, respectively. The mean period of the delivery-to-mortality for mothers was 5.92±3.48 days and the mean period of the intubation-to-mortality for mothers was 3.33±3.15 days. Conclusion: The risks of severe illness and death associated with COVID-19 increased in the third trimester compared to the first and second trimesters. All mortality cases involved unvaccinated pregnant women, of which most had at least one risk factor, obesity being the most prevalent. There was no COVID-19-related mortality in the newborns, and it was found that prematurity rates increased due to maternal disease.